ANALISIS KESALAHAN BERBAHASA TATARAN SINTAKSIS PADA KARANGAN SISWA KELAS VII SMP PGRI 1 KEDIRI - Elsa Aprilia (Universitas Islam Malang, 2022)
This study aims to describe the level of grammatical errors in the essays of seventh grade students of SMP PGRI 1 Kediri in the use of sentences. This research uses qualitative methods and descriptive research. The study in this research is in-depth and clearly gets the direction for the misuse of sentences at the syntactic level in student essay writing. In this study, data were collected through reading skills, note taking, and interviews for teachers and students. The data collection procedure consists of preparation, data collection, data analysis, and presentation of data analysis results. Data analysis techniques include identification, categorization, data presentation, and conclusion drawing. The results of this study prove that students make writing errors in the form of sentences that include four parts. Based on the findings, it shows that the reasons for language errors in students' writing are due to lack of attention to the use of grammar in writing, students' lack of vocabulary, and teachers' disinterest in them and providing sentence writing exercises.